Inter and intramolecular N-conjugate addition reactions using cinchona rerived primary amines - Ball, Anthony (2015)
This thesis describes the conjugate addition of nitrogen nucelophiles to alpha,beta-unsaturated enones using cinchona derived amines. Two separate projects are outlined within, intermolecular and intramolecular N-conjugate addition reactions.